Conservative Management of Mesenteric Panniculitis in a Remote Island - Paschalis Gavriilidis; Nicola de’ Angelis (Case Reports in Surgery)
Introduction. Mesenteric panniculitis (MP) includes a spectrum of nonspecific fibroinflammatory disorders of unknown aetiology that affects mainly the root of the mesentery. Case Report. A 68-year-old man is incidentally diagnosed with MP during follow-up investigation for a fusiform coeliac artery aneurysm. Four years since the diagnosis, he is completely asymptomatic. After discussing with him and presenting the current evidence, he decided not to proceed with biopsy because the finding was incidental and he is asymptomatic. Moreover, tumour markers were within the normal range. He has been scheduled for annual follow-ups with computerized tomography (CT) scans and tumour markers. Conclusions. MP is a rare chronic fibroinflammatory disease with contradictory evidence regarding its definition and management. Watchful follow-ups with CT scan and tumour markers are recommended for asymptomatic patients.